Rancang Bangun Mesin Perajang Singkong Multi Pisau - Sukadi; Novarini (Jurnal INOVATOR, 2018)
Cassava is a type of tuber that is very much found in the Jambi region. Cassava is easily damaged and decayed in a period of about two to five days after harvest, if it does not get good post-harvest treatment. It is necessary to process cassava crops into chips. To get the results of cassava chips that are good, there is a machine that can produce homogeneous chopped results. Besides that, it is expected that the cassava chopper machine can produce chopped with several forms of chopping. This study aims to make the design of multi-blade cassava chopper machines so that three types of chopping shapes can be produced with only one machine. Based on the results of the study, cassava chopper machines were produced with dimensions of length 630 mm wide by 390 mm and height of 450 mm. This machine uses a straight round multi-blade dish, waves and sticks. The capacity of this machine is 54 kg / hour and the power used is 185 watts.